Immunohaematopoietic stem and progenitor cell transplantation - a thirty year prospective and systematic research investigation - Jacobs, Peter (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DScMedSc (Medical Sciences)--University of Stellenbosch, 2010.